The design, synthesis and application of (thio)urea-based organocatalysts for a range of C-C bond transformations - Fleming, Eimear (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The identification and development of small chiral organic molecules capable of mimicking the hydrogen-bonding capabilities of enzymes is the main thrust of this thesis concerning the design and application of new (thio)urea containing catalysts for a variety of transformations. Herein we detail the development of a new class of binaphthyl (thio)urea catalysts and the evaluation of same in the asymmetric Friedel-Crafts reaction involving 7V-methyl indole and a range of both activated and deactivated nitrostyrenes. A suite of materials of varying steric and electronic characteristics were employed as catalysts in the enantioselective Friedel-Crafts addition reaction. Whilst enantioselectivity of the Friedel-Crafts adducts was found to be moderate (max. 50% ee), this was a significant improvement on the literature precedent, highlighting the difficulty of such a transformation.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.